2021
DOI: 10.1039/d0se01504k
|View full text |Cite
|
Sign up to set email alerts
|

Direct Z-scheme copper cobaltite/covalent triazine-based framework heterojunction for efficient photocatalytic CO2 reduction under visible light

Abstract: Copper cobaltite/covalent triazine-based framework hybrid photocatalysts with robust interfacial interactions were designed and synthesized for efficient photocatalytic CO2 reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…21−23 scheme heterostructure photocatalyst of COFs/inorganic semiconductors (TiO 2 , BiWO 6 ) had been reported by Zhang et al, which was synthesized via an in situ solvothermal method and the obtained photocatalysts showed high gas− solid photocatalytic CO 2 reduction efficiency under simulated sunlight irradiation. 21 Previously, our research group also reported a Z-scheme CuCo 2 O 4 /CTF-1 heterojunction photocatalyst for efficient CO 2 photoreduction to CO. 17 The result shows that the enhanced performance can be credited to the existence of special triazine ring with strong Lewis basicity and the formation of heterostructure, which increased the CO 2 adsorption ability and photoinduced electrons/holes separation proficiency. However, the counterparts of the COF-based heterojunction are usually metal oxides, which possess relatively weak CO 2 adsorption ability, perpetuating an opportunity to further increase the photoreduction activity of COF-based heterojunction materials.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…21−23 scheme heterostructure photocatalyst of COFs/inorganic semiconductors (TiO 2 , BiWO 6 ) had been reported by Zhang et al, which was synthesized via an in situ solvothermal method and the obtained photocatalysts showed high gas− solid photocatalytic CO 2 reduction efficiency under simulated sunlight irradiation. 21 Previously, our research group also reported a Z-scheme CuCo 2 O 4 /CTF-1 heterojunction photocatalyst for efficient CO 2 photoreduction to CO. 17 The result shows that the enhanced performance can be credited to the existence of special triazine ring with strong Lewis basicity and the formation of heterostructure, which increased the CO 2 adsorption ability and photoinduced electrons/holes separation proficiency. However, the counterparts of the COF-based heterojunction are usually metal oxides, which possess relatively weak CO 2 adsorption ability, perpetuating an opportunity to further increase the photoreduction activity of COF-based heterojunction materials.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, covalent organic frameworks (COFs), a novel class of organic porous materials, have appealed excessive attention in the CO 2 photoreduction field because of the well-designed pore structure, constituents of light elements (C, N, O), excellent stability, and wide light absorption performance, etc. Specially, the special triazine rings units could serve as Lewis basicity and linkages to various covalent bonds connected organic units (e.g., BO, CC, and CN), which endow COFs with particular advantages such as excellent CO 2 capture capability, enriched π-electrons delocalization effect. These superiorities are contributive to the advancement of CO 2 photoreduction activity. Nevertheless, the limited separation proficiency of photoinduced charge carriers in COFs still hampered its practical application. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the photocatalytic overall water-splitting reaction, the hydrogen evolution reaction (HER) generally proceeds simultaneously with the oxygen evolution reaction (OER). In comparison, the OER is significant in determining the reaction rate of water splitting, since the OER is a four-electron process with sluggish kinetics and multielectron transfer, including the dissociation of O–H bonds and the formation of O–O bonds. Naturally, the OER is an important metabolic process in photosynthesis, and this evolution has occurred for billions of years to lead to the oxygen-abundant atmosphere of Earth. Specifically, the solar-driven OER frees electrons and protons, which accumulate and subsequently convert CO 2 into carbohydrates .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of semiconductor photocatalysts possessing superior photocatalytic CO 2 reduction activity with CTFs is an effective method to synthesize composite photocatalysts that can inherit the advantages of both materials. 20–31 Tan and co-workers reported an organic–inorganic hybrid system (α-Fe 2 O 3 @Por-CTF-10×/Ru(Bpy) 3 Cl 2 ) photocatalytic system for CO 2 reduction. The system produces a catalytic CO evolution rate of 8.0 μmol h −1 with a 93% CO selectivity.…”
mentioning
confidence: 99%